2018
DOI: 10.5055/jom.2010.0001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intranasal fentanyl spray in patients with cancer and breakthrough pain

Abstract: Objective: This study reports the pharmacokinetics, tolerability, and safety of an intranasal fentanyl spray (INFS) in patients with cancer and breakthrough pain (BTP).Design: A randomized, open-label, two-period, crossover trial.Patients: Nineteen adult patients (mean 57.8 years) with BTP, receiving opioid treatment for chronic background pain, from clinical departments in Austria, France, and Norway entered and completed the study.Intervention: Patients were randomly assigned to receive one of six INFS dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…[67] To date, the pharmacokinetics of INFS and SLF have been reported in patients with cancer and BTP; in these studies, INFS and SLF demonstrated pharmacokinetics that were comparable between patients and healthy volunteers. [57,58]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[67] To date, the pharmacokinetics of INFS and SLF have been reported in patients with cancer and BTP; in these studies, INFS and SLF demonstrated pharmacokinetics that were comparable between patients and healthy volunteers. [57,58]…”
Section: Discussionmentioning
confidence: 99%
“…[58] Median t max values were between 12 and 15 minutes for INFS and the plasma concentration increased in a dose-dependent manner, although C max increased in a manner that was slightly less than proportional to the dose. Importantly, this study demonstrated that the pharmacokinetics of INFS in patients with cancer and BTP were comparable to previous results from studies in healthy volunteers.…”
Section: Current Treatments For Btpmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured and simulated plasma fentanyl concentrations increased, and increased adverse effects were seen from both subcutaneous and transdermal fentanyl [68]. A different study regarding the pharmacokinetics of intranasal fentanyl spray in patients with cancer was conducted to assess the tolerability and safety of this spray [69]. Neither of these studies measured the effect of the different formulations of fentanyl on cancer progression or the interaction with other drugs.…”
Section: Necessary Studies To Model Pk/pd Of Anaesthetics Drugs For C...mentioning
confidence: 99%
“…En otro estudio de 19 pacientes oncológicos con dolor irruptivo, la Tmax osciló entre 12 y 15 minutos en dependencia de la dosis (50; 100 y 200 mcg). La concentración plasmática fue dosis dependiente, aunque el aumento de la Cmax (0,35 a 1,2 ng/ml) fue algo inferior a la proporcionalidad de la dosis (56). En los preparados de administración intranasal los niveles plasmáticos en sangre arterial parecen predecir mejor la acción farmacodinámica de fentanilo.…”
Section: Solución Para Pulverización Nasal (Instanyl ® )unclassified